2010
DOI: 10.1007/s10823-010-9110-1
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Intergenerational Relations in a Multi-cultural Context: The Example of Filial Responsibility in Mauritius

Abstract: The purpose of this study is to explore attitudes towards filial responsibility amongst dyads of parents and young adult children using qualitative data from Mauritius, and to draw on the intergenerational solidarity-conflict and ambivalence frameworks to see whether they provide relevant interpretive tools for understanding these attitudes in a multi-cultural society. The study shows that although both generations agree that younger kin should support parents in later life, their motives vary: parents' attitu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…It is evident that social rules exert influence on the behaviour of children, because society can observe and judge attitudes in relation to care for elderly parents (Funk & Stajduhar 2009). Social rules on filial responsibility, as noted previously, make explicit the role of gender (Funk 2005; Hillcoat‐Nallétamby 2010). In this study, the women assumed the task of caring for a parent or husband as a natural obligation.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…It is evident that social rules exert influence on the behaviour of children, because society can observe and judge attitudes in relation to care for elderly parents (Funk & Stajduhar 2009). Social rules on filial responsibility, as noted previously, make explicit the role of gender (Funk 2005; Hillcoat‐Nallétamby 2010). In this study, the women assumed the task of caring for a parent or husband as a natural obligation.…”
Section: Discussionmentioning
confidence: 96%
“…This supports the debate on intergenerational relations in which the author asserts that there is 'an implicit contract in families which parents look after the children and hope they will care for them in old age' (Goldani 2004, p. 224). The expectation of care is built on family relationships throughout life and, therefore, depends on the bonds of affection, solidarity relationships of care for older people, values and beliefs transmitted between generations, as noted in other studies (Hillcoat-Nallétamby 2010). In this sense, the personal attitudes of filial responsibility are developed as teaching children to allow them in the future to provide care for their parents (Chappell & Funk 2009).…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, our findings show that despite having high levels of acculturation, younger immigrants still are highly committed to providing care to their ageing parents. Previous research has found that younger generations may feel obligated to support their parents out of a sense of reciprocity or gratitude (Hillcoat-Nallétamby, 2010; Yoo and Kim, 2010). It is possible that this sense of reciprocity remains strong even as individuals adjust to lives in a new culture.…”
Section: Discussionmentioning
confidence: 99%
“…It seems the two generations also differ in what they believe is important in filial expectation. Hillcoat-Nallétamby (2010) found that older parents’ beliefs about filial piety reflected cultural norms of obligation, while young adults felt they should support their parents out of a sense of reciprocity.…”
Section: Introductionmentioning
confidence: 99%
“…(52,53) This relational concept of personhood defined by relational ties between family members is also evident in other religions and societies throughout the world. (54)(55)(56)(57)(58) However, Kitwood and Buron suggest that a combination of relational and social elements contribute to individual conceptions of personhood within the dementia setting, while Bishop Merrill's study of American students suggests that there is a wider combination of individual, relational and innate elements to personalised defi nitions of personhood.…”
Section: Triad Of Personhood-related Considerationsmentioning
confidence: 99%